Staking Claims - Kilpatrick, Jeremy (NOMAD Nordic Studies in Mathematics Education, 1995)
The field of mathematics education has both scholarly and professional aspects. On the scholarly side, the question of what counts as research is still being debated. An examination of two proposed sets of criteria for evaluating the quality of research in mathematics education reveals that, interpreted appropriately, criteria borrowed from the natural and social sciences are relevant to a field that is attempting to be scientific. On the professional side, mathematics education must inevitably be concerned with the application of specialized knowledge to assist the students and teachers who are its clients. Teacher education remains a major function of mathematics education, parallel to the search for reliable knowledge to be applied. University mathematics educators need to work closely with mathematicians and with classroom teachers in developing both theory and practice. Mathematics education has flourished in countries in which institutional structures have supported it as an identifiable academic field.